Cryoglobulinemic vasculitis triggered by Staphylococcus aureus endocarditis with chronic hepatitis C virus co-infection: a case report and literature review - Reinberg, Céline; Vingerhoets, Sébastien; Pavlova, Olesya; Guenova, Emmanuella; Papadimitriou-Olivgeris, Matthaios; Comte, Denis (Frontiers in Immunology, 2024)
Infective endocarditis is a rare but life-threatening condition, occasionally linked to diverse immunologic manifestations, including mixed cryoglobulinemia. This can lead to cryoglobulinemic vasculitis, which has the potential for widespread organ damage. Although some cases have highlighted the relationship between infective endocarditis and cryoglobulinemic vasculitis, no comprehensive epidemiological evaluation or optimal treatment strategies have been advanced for such a combination. We present a case of methicillin-sensitive Staphylococcus aureus infective endocarditis associated with cryoglobulinemic vasculitis and conduct a literature review to compare management and outcomes in similar cases. Our patient presented with classical Meltzer’s triad and mild renal involvement. Cryoimmunofixation confirmed type III cryoglobulinemia, and serum cytokines showed elevated IL-6 levels. The differential diagnosis included infective endocarditis and chronic active hepatitis C virus infection. Rapid symptom resolution after antibiotic treatment identified infective endocarditis as the likely cause of cryoglobulinemic vasculitis. Our case and review of the literature highlight that early identification of the cause of cryoglobulinemic vasculitis is crucial for selecting appropriate treatment and preventing recurrence or morbidity.